Genetic Variations Associated with Energy Intake and Body Fat Composition in Healthy Korean Adults: A Genome-Wide Association Analysis. (29th May 2020) - Lee, Ga Young; Han, Sung Nim
Abstract: Objectives: Genetic variation contributes to individual differences in food preference, dietary habit, and nutrient intake, thus affecting nutritional status. Although studies which showed the relevance between genetic differences and the intake of nutrients such as carotenoid, vitamin E, and fat are available, more studies are needed for implementation of precision nutrition. Objective of the study was to investigate genetic variations that are associated with nutrient intake and taste sensitivity. Methods: A total of 100 healthy adults (50 men and 50 women) aged 25–35 y who were free of diseases were recruited. Anthropometric measurements, clinical parameters including CBC, lipid profile, glucose level, and liver function tests, dietary intake data using 3-day food record, and taste sensitivity for salty and sweet tastes were determined. A total of 800, 000 single nucleotide polymorphisms (SNPs) were analyzed by Theragen Etex using Theragen Precision Medicine Research Array (PMRA) chips. Results: A total of 577, 164 qualified SNPs were analyzed and three SNPs that might have significant relevance with energy intake (rs75052357, rs1125186, rs73471118) were identified. Carriers of the C allele in rs75052357 (C > T), which is identified in IQGAP1 loci, showed significantly higher fat mass (CC: 16.16 ± 3.52 kg, TC: 14.26 ± 3.58 kg, TT: 12.43 ± 3.83 kg) and higher % body fat (CC: 25.68 ± 5.40%, TC: 22.79 ± 6.10%, TT: 20.60 ± 7.52%) despite a lower energy intake (CC: 1782.2 ± 445.5 kcal, TC: 2212.5 ± 424.1 kcal, TT: 2315.0 ± 892.6 kcal). Carriers of G allele in rs1125186 (G > C) had significantly higher fat mass (CC: 13.34 ± 16.22 kg, CG: 16.22 ± 3.48 kg, GG: 15.67 ± 3.63 kg) in spite of lower energy intake compared with CC carriers (CC: 2222.5 ± 515.9 kcal, CG: 1927.9 ± 452.6 kcal, GG: 1745.7 ± 476.7 kcal). Carriers of T allele in rs73471118 (C > T) had significantly higher energy intake (CC: 1815.5 ± 445.0 kcal, TC: 2726.5 ± 490.6 kcal), while having lower threshold for sweet taste (CC: 8.94 ± 8.51 g/L TC: 0.40 ± 0.00 g/L). Conclusions: Novel SNPs showing associations between energy consumption and fat mass or sugar taste sensitivity have been identified. This finding can help developing personalized recommendation for energy intake, however, further studies to delineate the mechanisms are needed. Funding Sources: Supported by Seoul National University Research Grant in 2018.